Ethnic fractionalization and informal entrepreneurship: An institutional logics perspective - Mallon, Mark R.; Fainshmidt, Stav (Journal of Business Venturing, 2025)
Research is needed to uncover the sociocultural influences of informal entrepreneurship, or starting a legally unregistered but otherwise legitimate business. Using the institutional logics perspective, we posit that ethnic fractionalization increases the likelihood that entrepreneurs will not register their ventures because it fosters a clan logic and embeddedness in one's ethnic group. Entrepreneurs may not readily access knowledge regarding registration because the ethnic group can provide some of the benefits associated with registration. However, the clan logic is mitigated for entrepreneurs who receive advice from lawyers or businesspeople because these advisors are associated with the state or market logics, respectively, making knowledge of registration more accessible to entrepreneurs. We find support for these arguments using a sample of over 5000 entrepreneurs in 29 countries.